2015
DOI: 10.1177/2325967115621494
|View full text |Cite
|
Sign up to set email alerts
|

The Rotator Interval of the Shoulder

Abstract: Biomechanical studies have shown that repair or plication of rotator interval (RI) ligamentous and capsular structures decreases glenohumeral joint laxity in various directions. Clinical outcomes studies have reported successful outcomes after repair or plication of these structures in patients undergoing shoulder stabilization procedures. Recent studies describing arthroscopic techniques to address these structures have intensified the debate over the potential benefit of these procedures as well as highlight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…This finding indicated that the CHL could limit the downward movement of the shoulder joint; thus, the CHL could maintain the downward GH joint stability. Therefore, several scholars have proposed that, in the event that the shoulder joint becomes unstable in a certain direction, the RI could be closed to increase the downward shoulder joint stability [7,10].…”
Section: Analysis Of the Measured Data Of The Coracohumeral Ligament mentioning
confidence: 99%
“…This finding indicated that the CHL could limit the downward movement of the shoulder joint; thus, the CHL could maintain the downward GH joint stability. Therefore, several scholars have proposed that, in the event that the shoulder joint becomes unstable in a certain direction, the RI could be closed to increase the downward shoulder joint stability [7,10].…”
Section: Analysis Of the Measured Data Of The Coracohumeral Ligament mentioning
confidence: 99%
“…32 Our understanding of the RI can help us treat the shoulder during arthroscopic intervention in conditions such as adhesive capsulitis or shoulder instability. 39,44 The relatively new finding of an anatomical structure in the RI like the CGL may continue to change our knowledge about shoulder biomechanics and further clarify identification and clinical management of pathologic processes. Additional studies are needed to clarify the role of the RI and RC and its associated structures in the setting of shoulder instability to better define indications and improve surgical techniques.…”
Section: Resultsmentioning
confidence: 99%
“…The proximal humeral ligamentous stability is primarily provided by four ligaments: coracohumeral ligament superior glenohumeral ligament, middle glenohumeral ligament, and inferior glenohumeral ligament (Figure 1). The coracohumeral ligament strengthens the rotator interval, which is a triangular space located in the anterosuperior aspect of the shoulder that contributes to stability of the glenohumeral joint 12,14. The superior glenohumeral ligament resists inferior translation with the arm at the side (0 degrees abduction), the middle glenohumeral ligament resists anterior to posterior translation at approximately 45 degrees of abduction, and the inferior glenohumeral ligament resists anterior to posterior translation at 90 degrees of abduction 9,14.…”
Section: Discussionmentioning
confidence: 99%